Mathematics Stack Exchange is a question and answer site for people studying math at any level and professionals in related fields. Join them; it only takes a minute:

Sign up
Here's how it works:
  1. Anybody can ask a question
  2. Anybody can answer
  3. The best answers are voted up and rise to the top

I have an equation of the form:

$$f(s)=g(s)\exp(ih(s))f(b-s), \qquad (b \in \mathbb{R}, s \in \mathbb{C})$$

where $f:\mathbb{C} \to \mathbb{C}$, $g(s)>0$, $h(s) \in (-\pi,\pi]$.

We can prove that if $h(s) \neq 0$ then $f(s)=0$, $f(b-s)=0$ (I know that if $f(s)=0$ then $f(b-s)=0$). However the case $h(s)=0$ does not imply this case directely. But we can see also that we can have $f(s)=0$, $f(b-s)=0$ if $h(s)=0$.

(a) My question is how to deal with the case when $h(s)=0$.

(b) How I can solve this functional equation: $g(1-s)g(s)=1$ with respect to $g$ for all $s$.

share|cite|improve this question
If $g(s)>0$ and $h(s)\in(-\pi,\pi]$, shouldn't the codomain of $g$ and $h$ be $\mathbb R$? Also, is the equation supposed to be true for all $s\in\mathbb C$ and all $b\in\mathbb R$, or for all $s$ and a particular $b$, or what? – Rahul Dec 30 '12 at 13:06
Yes, Done. The equation hlods for all $s$ and some $b$ including $b=1$. I am searching for the roots of $f(s)=0$ when $b=1$. – ZE1 Dec 30 '12 at 13:14

Fix $b \in \mathbb{R}$ and suppose that $f(s) = g(s)\exp(ih(s))f(b-s)$ for all $s \in \mathbb{C}$. As $g(s) > 0$ and $\exp(ih(s)) \neq 0$, $f(s) = 0$ if and only if $f(b - s) = 0$. Depending on $f$, there may not be any zeroes, but if there is a zero $s_0$, then $b - s_0$ is another zero.

Now suppose $b = 1$ as in your comment, then we have

$$f(s) = g(s)\exp(ih(s))f(1-s)$$


$$f(1-s) = g(1-s)\exp(ih(1-s))f(s)$$


\begin{align*} f(s) &= g(s)\exp(ih(s))f(1-s)\\ &= g(s)\exp(ih(s))[g(1-s)\exp(ih(1-s))f(s)]\\ &= g(s)g(1-s)\exp(ih(s) + ih(1-s))f(s). \end{align*}

Provided $f$ has isolated zeroes (as in the case of a non-zero holomorphic function), we see that

$$1 = g(s)g(1-s)\exp(ih(s) + ih(1-s))$$

and therefore

$$g(s)g(1 - s) = \frac{1}{\exp(ih(s) + ih(1-s))} = \exp(-ih(s)-ih(1-s)).$$

For an arbitrary $b$, the same manipulations give

$$g(s)g(b - s) = \exp(-ih(s)-ih(b-s)).$$

share|cite|improve this answer

Your Answer


By posting your answer, you agree to the privacy policy and terms of service.

Not the answer you're looking for? Browse other questions tagged or ask your own question.